Analysis of space-charge-limited conduction mechanisms in ZrON/SiC system / Nur Hasdyanna Hasnurashid - Nur Hasdyanna, Hasnurashid (2020)
In this study, current conduction mechanism by space-charge-limited conduction (SCLC) and Poole-Frenkel (PF) emission on ZrON/SiC system that was oxidized and nitrided in N2O at various temperatures (400-900˚C) were analysed. The current-voltage (I-V) measurements were performed in Al-gate metal-oxide-semiconductor (MOS) capacitor by sputtering of Al film on top of the film and at the back of the substrate. Then, characterization of electrical properties was done according to two types of bulk-limited conduction, which are space-charge-limited conduction and Poole-Frenkel emission conduction. Space-charge-limited conduction and Poole-Frenkel emission have been systematically evaluated through data analysis method by the fitting of linear regression according to Ohm’s Law model in J-Vg plot and Poole-Frenkel model in ln (J/E)-E1/2 plot. The mechanisms of the interface traps and the current conducted through oxides were affected by the temperature of simultaneous oxidation and nitridation performed on the sputtered Zr on SiC substrate. Electrical results showed that sample that was oxidized/nitrided Zr/SiC for 15-min duration at 500˚C recorded the highest electric field breakdown (EB) of 5.05 MV/cm at 10-6 A/cm2. Based on the current density and electric field (J-E) plot, the space-charge-limited conduction mechanism by Ohm’s law was analysed. It is found that Ohm’s law conduction occurs at low electric field (-0.4 – 0.05 MV/cm). As for Poole-Frenkel emission, the conduction mechanism occurs at higher electric field range (0.6-1.65 MV/cm). The effect of different oxidation and nitridation temperature on leakage current and electric field breakdown at were compared and discussed.